PENGARUH KOMPETENSI ANDRAGOGI DAN KOMUNIKASI INTERPERSONAL TERHADAP KEMAMPUAN MANAJERIAL TUTOR DI BALAI LATIHAN KERJA DKI JAKARTA - Durotul Yatimah; Karta Sasmita; Daddy Darmawan; Rahmat Syah (Jurnal Pendidikan dan Pemberdayaan Masyarakat (JPPM), 2020)
This study aims to analyze the influence of the skills of andragogy and interpersonal communication tutor at BLK DKI Jakarta. The research method uses correlational and associative quantitative research. The research was conducted at BLK DKI Jakarta by sampling as much as 120 purposive from a total of 170 tutors scattered in BLK DKI Jakarta. Data retrieval by developing instruments using questionnaires. Data analysis using multiple regression analysis with the multivariate test. The results showed that first there was a significant influence between andragogy competence of tutoring ability of the tutor, both there is an influence between interpersonal communication to the management skills of the tutor as well as third Simultaneous influence between Andragogical's compliance and interpersonal communication on the managerial skills of tutors at BLK DKI Jakarta.   The implications of this research is an attempt to improve the managerial skills and competence of tutors can be done through improved andragogy competence and interpersonal communication.